Literasi Keuangan dan Digitalisasi UMKM serta Warung Kecil di Desa Karangmulya, Kecamatan Jamanis, Kabupaten Tasikmalaya - Yadi; Ismayanti; Muh Fajar Fazriansyah; Neng Sopiah; Hary Lesmana Surya; Muhammad Rovi; Arif Amril Mubarok; Dede Riswandi (LPPM Politeknik Piksi Ganesha, 2025)
Abstract: This community service program focused on enhancing financial literacy and supporting the digitalization of micro, small, and medium enterprises (MSMEs) and small retailers in Karangmulya Village, Tasikmalaya. Although digital transactions are rapidly growing in Indonesia, many rural businesses still rely on cash and have limited access to digital financial services. To address this challenge, the program introduced the Quick Response Code Indonesian Standard (QRIS) in collaboration with Bank Indonesia as a safe, practical, and efficient payment solution. Methods included seminars, workshops, QRIS transaction simulations, and mapping MSME locations on Google Maps to increase visibility. The results showed that participants better understood the benefits of digital payments and felt more confident applying QRIS in their daily business activities. Challenges encountered included unstable internet connections and the readiness of senior business owners to adapt. Nevertheless, the program demonstrated that village-based financial literacy initiatives can effectively accelerate financial inclusion while strengthening local economic resilience. Keywords: Digital literacy, QRIS, MSMEs, financial inclusion, rural economy Abstrak: Program pengabdian kepada masyarakat ini berfokus pada peningkatan literasi keuangan serta dukungan digitalisasi UMKM dan warung kecil di Desa Karangmulya, Tasikmalaya. Meski transaksi digital berkembang pesat di Indonesia, banyak pelaku usaha di pedesaan masih mengandalkan pembayaran tunai dan minim akses terhadap layanan keuangan digital. Untuk menjawab tantangan tersebut, program ini memperkenalkan penggunaan Quick Response Code Indonesian Standard (QRIS) melalui kerja sama dengan Bank Indonesia sebagai solusi pembayaran yang aman, praktis, dan efisien. Metode yang digunakan mencakup seminar, lokakarya, simulasi transaksi QRIS, serta pemetaan lokasi UMKM pada Google Maps agar lebih mudah dijangkau masyarakat. Hasil kegiatan menunjukkan peserta memahami manfaat pembayaran digital dan lebih percaya diri menggunakan QRIS dalam aktivitas usaha. Kendala yang ditemui adalah keterbatasan internet dan kesiapan pelaku usaha senior. Meski demikian, program ini membuktikan literasi keuangan berbasis desa dapat mempercepat inklusi keuangan sekaligus memperkuat ketahanan ekonomi lokal. Kata Kunci: Literasi keuangan, QRIS, UMKM, inklusi keuangan, ekonomi desa